CTG-Repeat Detection in Primary Human Myoblasts of Myotonic Dystrophy Type 1 - Hintze, Stefan; Mensel, Raphaela; Knaier, Lisa; Schoser, Benedikt; Meinke, Peter (Frontiers in Neuroscience, 2021)
Myotonic dystrophy type 1 (DM1) is an autosomal dominant multisystemic disorder caused by unstable CTG-repeat expansions in the DMPK gene. Tissue mosaicism has been described for the length of these repeat expansions. The most obvious affected tissue is skeletal muscle, making it the first target for therapy development. To date there is no approved therapy despite some existing approaches. Thus, there is the demand to further advance therapeutic developments, which will in return require several well-characterized preclinical tools and model systems. Here we describe a modified method to identify the CTG-repeat length in primary human myoblasts isolated from DM1 patients that requires less genomic DNA and avoids radioactive labeling. Using this method, we show that primary human DM1 myoblast cultures represent a population of cells with different CTG-repeat length. Comparing DNA from the identical muscle biopsy specimen, the range of CTG-repeat length in the myoblast culture is within the same range of the muscle biopsy specimen. In conclusion, primary human DM1 myoblast cultures are a well-suited model to investigate certain aspects of the DM1 pathology. They are a useful platform to perform first-line investigations of preclinical therapies.